'I didn't have a clue what we were doing': (not) engaging 16 and 17 year old Voters in Scotland. Issue 3 (August 2014) - Stewart, Ellen A.; Wilson, Iain; Donnelly, Peter D.; Greer, Scott L.
<x xml:space="preserve">Abstract</x> Calls to extend the franchise to 16 and 17 year olds are gaining ground, with the 2014 Referendum on Scottish Independence potentially acting as a test ground for wider reforms. Debates on the relative merits of this decision aside, there is little practical experience of registering and engaging young people with major elections in the Scottish context. This article reports research on pilot Health Board Elections held in two areas of Scotland in 2010. 16 and 17 year olds were entitled to vote in these elections, and yet many were excluded by difficulties with registration, and turnout among those who did register was strikingly low. Drawing on focus groups in local schools, we draw out some key lessons for future efforts to engage young voters in Scotland.